2017
DOI: 10.5897/err2016.3106
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing Chinese International students studying in the United States

Abstract: Chinese international students often find it challenging to adjust to attending college in the United States (US). There is limited research addressing Chinese international college students' adjustment in the US. Drawing on what literature exists combined with research addressing Chinese immigrants' transition and international students' transition, this article examines strategies to help Chinese international students successfully make this adjustment. Educating the Chinese international students, educators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 46 publications
(101 reference statements)
3
21
0
Order By: Relevance
“…Academic difficulties are issues related to the teaching and learning processes during lectures and fulfilling school work. This finding coincides with those of numerous previous researchers, who have reported that academic stress and pressure to succeed are experienced by Asian students studying in the United States and Western students studying in China [ 29 , 102 , 103 ]. Similarly, significant differences were found regarding online facilitation and the personality traits openness, conscientiousness, and agreeableness, with degree-seeking students rating higher than short-term exchange students.…”
Section: Discussionsupporting
confidence: 92%
“…Academic difficulties are issues related to the teaching and learning processes during lectures and fulfilling school work. This finding coincides with those of numerous previous researchers, who have reported that academic stress and pressure to succeed are experienced by Asian students studying in the United States and Western students studying in China [ 29 , 102 , 103 ]. Similarly, significant differences were found regarding online facilitation and the personality traits openness, conscientiousness, and agreeableness, with degree-seeking students rating higher than short-term exchange students.…”
Section: Discussionsupporting
confidence: 92%
“…However, language barriers are the main barrier for Chinese international students. Chinese traditional pedagogy contributes to the adaptation and success of Chinese international students (e.g., Ching et al, 2017). Chinese students feel it is hard to speak out and present in the classroom (e.g., Lin et al, 2019;Wu et al, 2015).…”
Section: Research Focusing On Chinese International Students Before Covid Timesmentioning
confidence: 99%
“…The transition to college life, and to a potentially more diverse and more multicultural environment on the university campus, always brings new demands and challenges to international students (Ruberman, 2014). These demands and challenges are especially acute for racial and cultural minority international students from Asian countries (Ching et al, 2017). For example, Sherry et al (2010) found that Asian international students often feel culturally misunderstood and socially isolated in the university community.…”
Section: International College Studentsmentioning
confidence: 99%